The palliative care scorecard as an innovative approach in long-term care - Esslinger, Adelheid Sussanne (Igitur, Utrecht Publishing & Archiving, 2009)
INTRODUCTION: In long-term care facilities professional concepts for palliative care are of great interest as individual needs of clients (residents, relatives, and friends) are in the focus of services. CASE: Within a long-term care facility of the Red Cross Organization in Germany, we developed a palliative care concept in 2008. It is integrated in the strategy of the whole organization. As the strategic management concept is based on the balanced scorecard, we introduced a palliative care scorecard. The facility offers 200 places for residents. It has established 27 strategic targets to achieve. One of these is to provide individual care. Another one is to integrate relatives of residents. One more deals with the integration of volunteers. We decided to implement a palliative care concept within the target system (e.g. develop individual pain therapy, create and coordinate interdisciplinary palliative care teams). RESULTS: The case shows how it is possible to integrate and strengthen the subject of palliative care within the existing management system of the organization. In order to translate the concept into action, it will be necessary to change the organizational culture into an ‘open minded house’. This especially means that all members of the organization have to be trained and sensitized for the matters of care at the end of life. CONCLUSION: The development and implementation of an integrated concept of palliative care, which fits into the existing management system, is the base of a sustainable offer of specialized care for the residents and their social network. Therefore, not only the quality of care and life of the clients, but also the surviving of the facility on the market of care will be assured.